Assessment of the Dhobikhola river water using real-time monitoring system - Adhikari, Mandira Pradhananga; Rawal, Narendra Bahadur; Yadav, Kabita (BIBECHANA, 2025)
River water quality inside the Kathmandu Valley is deteriorating day to day by the mixing of untreated industrial and domestic waste. Till now, a few researchers characterised the water quality of Dhobikhola using traditional methods, therefore, there is a lack of enough data to identify river water quality thoroughly. With the exponential development of information technology, continuous, fine-scale and real-time data monitoring is possible using advanced sensor probes with sophisticated data logging systems, it would be the first practice in the case of the Dhobikhola River. In this study, real-time continuous monitoring and collection of large data using sophisticated sensors were performed to determine the river water quality and the sources of pollutants. The spatial variation of water quality parameters indicated that after entering the core city area most parameters such as conductivity and turbidity changed more than four times and oxidation-reduction potential (ORP) turned into a negative value. The high conductivity and negative ORP values are the indication of sewer connection. Daily and diurnal variations suggested that the Dhobikhola River is always polluted with a negative ORP value (< -50mV). All the results suggest that it is enormously important to control the mixing of effluent into the Dhobikhola Rivers to revive the ecology of the aqueous system.